Analysis of consumer shopping motivation on TikTok live streaming using the SEM-SmartPLS test approach - Intan Lidiya Widuri (Privietlab, 2026)
The development of TikTok live streaming has driven changes in consumer shopping behavior in social media-based e-commerce, particularly through informative, persuasive, and entertaining real-time interactions. This study aims to analyze consumer shopping motivation on TikTok live streaming by examining the influence of seller characteristics, streaming platform, and performance on purchase motivation through customer perceived value. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using SmartPLSThe data was collected through questionnaires distributed to respondents who had made or considered making purchases through TikTok Live. The model was evaluated through construct validity and reliability testing, determination coefficients, and an analysis of direct and indirect effects between variables. The results of the study show that all constructs have excellent validity and reliability. Seller characteristics and the streaming platform have a significant effect on performance and customer perceived value. Furthermore, performance was proven to significantly increase customer perceived value. The main results of this study indicate that customer perceived value is the most dominant factor influencing purchase motivation and acts as the main mediating variable between seller characteristics, platform quality, and live streaming performance on purchase motivation. This study concludes that consumer shopping motivation on TikTok live streaming is formed through an integrated mechanism, with consumer value perception as the main determinant in driving purchase decisions.